2022
DOI: 10.3389/fphar.2022.920779
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Research on the Effects and Mechanisms of Chemokines and Their Receptors in Cancer

Abstract: Cancer is a common and intractable disease that seriously affects quality of life of patients and imposes heavy economic burden on families and the entire society. Current medications and intervention strategies for cancer have respective shortcomings. In recent years, it has been increasingly spotlighted that chemokines and their receptors play vital roles in the pathophysiology of cancer. Chemokines are a class of structurally similar short-chain secreted proteins that initiate intracellular signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…It’s known that different immune cell subsets can be recruited into TME via interactions between chemokines and chemokine receptors, and affect tumor progression and therapeutic outcome [ 66 ]. Chemokines (CXCL12 [ 67 ], CXCL8 [ 68 ], CXCL5 [ 69 ]) and chemokine receptors (CXCR1/2 [ 70 ], CCR4 [ 71 , 72 ], CCR8 [ 73 ]) are well-known to deeply participate in the tumor development and progression in various cancers, including LUAD [ 74 ]. In the present study, we found that the expression of KIAA1199 was correlated with the levels of many chemokines (CXCL12, CXCL8, CXCL5) and chemokine receptors (CXCR1/2, CXCR4, CCR8) in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…It’s known that different immune cell subsets can be recruited into TME via interactions between chemokines and chemokine receptors, and affect tumor progression and therapeutic outcome [ 66 ]. Chemokines (CXCL12 [ 67 ], CXCL8 [ 68 ], CXCL5 [ 69 ]) and chemokine receptors (CXCR1/2 [ 70 ], CCR4 [ 71 , 72 ], CCR8 [ 73 ]) are well-known to deeply participate in the tumor development and progression in various cancers, including LUAD [ 74 ]. In the present study, we found that the expression of KIAA1199 was correlated with the levels of many chemokines (CXCL12, CXCL8, CXCL5) and chemokine receptors (CXCR1/2, CXCR4, CCR8) in LUAD.…”
Section: Discussionmentioning
confidence: 99%